ChemCourse: Design of an ESP Course for Chemists and Chemistry Students - Bula Villalobos, Olmedo; Díaz-Ducca, Jenaro Alberto (Revista de Lenguas Modernas, 2017)
This article presents the design process of an English for Specific Purposes (ESP) course addressed to hemistry students and chemists at the school of chemistry, University of Costa Rica. This process required a needs analysis to assess the students’ academic and professional needs, wants, and lacks in order to create a course that included the four macro skills: speaking, listening, reading, and writing. This article presents the findings of the needs analysis. In addition, a set of learning strategies were considered in the design process (paraphrasing, negotiation of meaning, predicting, scanning, among others) to fit the students’ reported needs. Based on the findings of the needs analysis, ChemCourse was designed to respond to students’ needs, wants, and lacks. ChemCourse was developed as a fifteen-week, ESP course within a task-based language teaching (TBLT) approach. The content of the course was divided into five units. Este artículo presenta el proceso de diseño de un curso de inglés para fines específicos (ESP) dirigido a estudiantes de química y químicos de la Escuela de Química de la Universidad de Costa Rica. Este proceso requirió un análisis para evaluar las necesidades profesionales y académicas de los estudiantes, sus intereses y carencias para crear un programa educativo que incluyera las cuatro macrodestrezas: habla, escucha, lectura y escritura. Además, una serie de estrategias de aprendizaje se consideraron en el proceso de diseño (parafraseo, negociación de significado, predicciones, escaneo, entre otras) para coincidir con las necesidades reportadas por los estudiantes. Basado en los resultados del análisis de necesidades, ChemCourse se diseñó para responder a sus requerimientos, intereses y carencias. ChemCourse se implementó como un curso de ESP de quince semanas dentro de un enfoque fundamentado en el desarrollo de tareas para la enseñanza de idiomas. El contenido quedó divido en cinco unidades.